Gender-dependent differences of mitochondrial function and oxidative stress in rat skeletal muscle at rest and after exercise training. (2nd November 2017) - Farhat, Firas; Amérand, Aline; Simon, Bernard; Guegueniat, Nathalie; Moisan, Christine
ABSTRACT: Objective: This study investigated gender-dependent differences of mitochondrial function and sensitivity to in vitro ROS exposure in rat skeletal muscle at rest and after exercise training. Methods: Wistar rats underwent running training for 6 weeks. In vitro measurements of hydroxyl radical production, oxygen consumption (under basal and maximal respiration conditions) and ATP production were made on permeabilized fibers. Mitochondrial function was examined after exposure and non-exposure to an in vitro generator system of reactive oxygen species (ROS). Antioxidant enzyme activities and malondialdehyde (MDA) content were also determined. Results: Compared with sedentary males, females showed a greater resistance of mitochondrial function (oxygen consumption and ATP production) to ROS exposure, and lower MDA content and antioxidant enzyme activities. The training protocol had more beneficial effects in males than females with regard to ROS production and oxidative stress. In contrast to male rats, the susceptibility of mitochondrial function to ROS exposure in trained females was unchanged. Discussion: Exercise training improves mitochondrial function oxidative capacities in both male and female rats, but is more pronounced in males as a result of different mechanisms. The resistance of mitochondrial function to in vitro oxidative stress exposure and the antioxidant responses are gender- and training-dependent, and may be related to the protective effects of estrogen.